Proceedings of the Erice workshop: A new baseline for the hybrid, asymmetric, linear Higgs factory HALHF - Brian Foster; Erik Adli; Timothy L. Barklow; Mikael Berggren; Stewart Boogert; Jian Bin Ben Chen; Richard D’Arcy; Pierre Drobniak; Sinead Farrington; Spencer Gessner; Mark J. Hogan; Daniel Kalvik; et al. (Physics Open)
The HALHF collaboration has discussed a new baseline for the project, taking into account comments from the accelerator community on various aspects of the original design. In particular, these concerned the practicality of the dual-purpose linac to accelerate both colliding positron bunches and the drive beams required for the plasma linac. In addition, many other aspects of the project were also considered; the discussion and conclusions are documented in this paper. Finally, a new baseline is outlined that has been optimised and addresses several weaknesses in the original design, has higher luminosity, reduced centre-of-mass energy boost and additional features such as two interaction points and positron polarisation as well as electron polarisation. Although HALHF has become longer and more expensive, it remains significantly smaller and cheaper than other mature Higgs factory designs currently under discussion.